Compact tunable bandpass filter with wide tuning range and enhanced stopband characteristics. Issue 16 (1st August 2013) - Zhao, B.L.; He, Z.T.; Wei, X.B.; Shi, Y.
Abstract : A compact tunable bandpass filter (BPF) with wide tuning range and enhanced stopband characteristics based on low‐temperature co‐fired ceramic technique is proposed. The wide tuning range is realised by properly introducing an axial coupling structure. Three transmission zeros are obtained near the passband for enhanced frequency selectivity by introducing mixed electric/magnetic (E/M) coupling between the source/load and the taped inductor. Back‐to‐back varactor diodes are adopted to improve linearity characteristics. A tunable BPF with a 120% tuning range from 370 to 850 MHz has been designed and fabricated to verify the proposed design concept. The measured results are in good agreement with the electromagnetic simulation. The circuit occupies only 4.0 × 3.0 × 1.6 mm 3 .